Numerical CFD investigation of liquid-liquid two-phase flow separation in a microseparator - Lu, I.-L. (Taylor and Francis Ltd., 2021)
Two-phase flow liquid-liquid separation in a microseparator has promising use in microfluidic field such as downstream biodiesel purification. The present study aims to investigate the effect of daughter channel (DC) geometry on liquid-liquid separation in a new design of microseparator. Olive oil and water were selected as continuous and dispersed phase, respectively. Different DC intervals (500â1000Â Âµm) and angles (60Â°-120Â°) were designed to generate nine single-sided DC microseparator configurations. Further, these were arranged in mirrored configurations to generate nine double-sided DC microseparator configurations. At continuous phase flow rate (QCP) of 0.5Â ml/h, interval of 500Â Âµm and angle of 90Â° achieved best performance with highest oil purity of 100 in secondary channel outlet (SCOutlet) and lowest oil purity of 26 in main channel outlet (MCOutlet). The results revealed that the design of DC with lower pressure drop led to better separation performance. Furthermore, the occurrence of Jamin effect in the DC could cause hindrance in the two-phase flow liquid-liquid separation. The use of double-sided DC microseparator configuration further improves the separation performance. Overall, an excellent separation of oil was successfully achieved. Â© 2021 Taylor & Francis Group, LLC.